Peran perangkat adat desa dalam penyelesaian sengketa: Pendekatan hukum peradilan adat di Aceh - Rohimah, Na'imatur (Maliki Interdisciplinary Journal, 2023)
Customary and customary law is useful as a guide tool so that it is precise in determining the behavior and also the attitude that must be carried out in accordance with customary law. This writing aims to study the legal basis, structure and scope of responsibility of traditional leaders, the objectives and principles of customary justice and the implementation of customary court decisions. This research uses normative and empirical law. Aceh customary court dispute resolution is based on the fourth Pancasila precept, the atra of which has been recognized by national law in Indonesia. The purpose of customary justice is to create peace and balance in society and protect the rights of people who are in dispute so that they can reconcile. The gampong and mukim courts have their administrative apparatus, the chairman of the session is the keuchik, the clerk is the gampong secretary, the meunasah priest, tuha peut and scholars as members. Whereas in mukim, the method of dispute resolution is attended by traditional leaders, imeum meukim as chairman of the session, imeum chik as clerk, tuha peut, secretary of mukim and scholars' as members. In carrying out his decision, the keuchik determines the place and time according to the mutual agreement.